2020
DOI: 10.2169/internalmedicine.3907-19
|View full text |Cite
|
Sign up to set email alerts
|

<i>Pneumocystis jirovecii</i> Pneumonia in a Patient with Breast Cancer Receiving Neoadjuvant Dose-dense Chemotherapy

Abstract: We herein report a 38-year-old woman with breast cancer who developed Pneumocystis jirovecii pneumonia (PCP) during neoadjuvant dose-dense chemotherapy combined with dexamethasone as antiemetic therapy. Chest computed tomography showed bilateral ground-glass opacities and consolidation. The serum β-Dglucan levels were elevated, and P. jirovecii DNA was detected from the bronchoalveolar lavage fluid by polymerase chain reaction. Her clinical findings improved with trimethoprim/sulfamethoxazole and adjunctive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Pneumocystis jirovecii pneumonia (PCP) remains a life-threatening, opportunistic disease related to T cell suppression, macrophage defect, or other immunodeficiencies. New treatments and higher life expectancies in various oncologic or immune disease illustrate that PCP among non-AIDS patients is steadily increasing [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Pneumocystis jirovecii pneumonia (PCP) remains a life-threatening, opportunistic disease related to T cell suppression, macrophage defect, or other immunodeficiencies. New treatments and higher life expectancies in various oncologic or immune disease illustrate that PCP among non-AIDS patients is steadily increasing [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…While TMP-SMX is commonly endorsed for PCP prophylaxis in breast cancer patients undergoing chemotherapy [ 15 ], and the general recommendation for PCP prophylaxis in adults, including cancer patients, is a single-strength or double-strength tablet once daily [ 16 ]. Furthermore, while it is generally reported that relapses of PCP often occur in cases of poor adherence to prophylactic medication [ 8 ], considering that adherence was maintained, in this case, the optimal usage, particularly in individuals with distinct clinical profiles, warrants a more thorough exploration [ 4 , 5 ]. To tailor PCP prophylaxis management individually, further exploration of information, including the search for additional relevant factors, is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumocystis pneumonia (PCP) is a severe condition predominantly found in immunocompromised individuals, with a less than 5% prevalence in most risk groups [1]. Although breast cancer is not typically linked to immunosuppression, reports have indicated an increased risk of PCP incidence in patients undergoing high-dose chemotherapy or receiving corticosteroids [2][3][4][5][6]. The prognosis for breast cancer patients who develop Pneumocystis jirovecii pneumonia can be severe, with a mortality rate of 40% reported in a study of patients with solid tumors, including breast cancer, making prevention crucial [3].…”
Section: Introductionmentioning
confidence: 99%
“…With the approval of pegfilgrastim, a long-acting G-CSF preparation, in September 2014, dose-dense therapy became widely used in Japan. Along with this, there are isolated case reports and one case series of PJP during dose-dense neoadjuvant chemotherapy for breast cancer [ 4 , 6 - 7 ].…”
Section: Discussionmentioning
confidence: 99%